“Just Throw It Behind You and Just Keep Going”: Emotional Labor when Ethnic Minority Healthcare Staff Encounter Racism in Healthcare - Ahlberg, Beth Maina; Hamed, Sarah; Bradby, Hannah; Moberg, Cecilia; Thapar-Björkert, Suruchi (Frontiers in Sociology, 2022)
Encountering racism is burdensome and meeting it in a healthcare setting is no exception. This paper is part of a larger study that focused on understanding and addressing racism in healthcare in Sweden. In the paper, we draw on interviews with 12 ethnic minority healthcare staff who described how they managed emotional labor in their encounters with racism at their workplace. Data were analyzed using thematic analysis. The analysis revealed that experienced emotional labor arises from two main reasons. The first is the concern and fear that ethnic minority healthcare staff have of adverse consequences for their employment should they be seen engaged in discussing racism. The second concerns the ethical dilemmas when taking care of racist patients since healthcare staff are bound by a duty of providing equal care for all patients as expressed in healthcare institutional regulations. Strategies to manage emotional labor described by the staff include working harder to prove their competence and faking, blocking or hiding their emotions when they encounter racism. The emotional labor implied by these strategies could be intense or traumatizing as indicated by some staff members, and can therefore have negative effects on health. Given that discussions around racism are silenced, it is paramount to create space where racism can be safely discussed and to develop a safe healthcare environment for the benefit of staff and patients.